(untitled) (Bangladesh Journal of Botany, 2023)
Effects of different tillage management on the growth and yield of maize were studied from early June to September 2017. The experiment was set up with three tillage treatments: traditional shallow moldboard plow tillage with straw removal (MT), sub-soiling/ plow tillage /sub-soiling rotation with straw mulch (ST) and no-till/sub-soiling/no-till rotation with straw retention (NT). The soil compaction of different soil layers, plant height, chlorophyll content, above-ground biomass and yield were determined through the three tillage practices. Results showed that NT and ST treatments helped to reduce soil compaction, and had a positive effect on maize root growth and development, plant height and chlorophyll content compared to the MT treatment. The chlorophyll value in early growth period under NT and ST increased by 31.8 and 24.6%, respectively, and the plant height was increased by 20.2 and 15.9% compared with MT, respectively. The size order of soil compaction was MT > NT > ST, and the soil compaction value was the maximum at 20 cm under MT treatment, which was 1007 kPa. Meanwhile, NT and ST also increased the plant above-ground biomass and yield of maize. Compared to MT treatment, the dry weight of plants for the NT and ST treatments significantly increased by 24.3 and 15.7%, respectively, and the grain yield significantly increased by 11.9 and 14.9%, respectively (P < 0.05). NT and ST tillage treatments are effective measures to improve structure of soil, contribute to plant growth and development and thereby increase in yield. Bangladesh J. Bot. 52(2): 451-458, 2023 (June) Special